The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1432-2277.2006.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT angiography in live donor renal transplantation: experience from 156 consecutive cases at a single centre

Abstract: Summary The performance of multidetector computed tomography (CT) angiography was assessed in the pre‐operative evaluation of live renal donors. Between July 1998 and March 2006, 156 consecutive patients underwent open donor nephrectomy following pre‐operative multidetector CT angiography (MDCTA). Operative notes were compared with radiological reports and discrepancies identified. MDCTA missed five of 28 accessory arteries (four visible with hindsight), accuracy of 96%. Of 30 early‐branching renal arteries, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
1
23
2
Order By: Relevance
“…Risk stratification based on most radiographic findings is largely opinion-based and may be influenced by the type of imaging modality used (42). We found that 132 (6.7%) of 1957 of our potential donors had radiographic abnormalities of the renal arteries or kidneys that were perceived as contraindications for kidney donation, compared with 38 (11%) of 333 (42), 5 (4.0%) of 126 (16), and 3 (1.9%) of 159 (43) in other studies that used CT angiography/urography. This discrepancy between centers suggests a need for further research on the clinical relevance of these abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…Risk stratification based on most radiographic findings is largely opinion-based and may be influenced by the type of imaging modality used (42). We found that 132 (6.7%) of 1957 of our potential donors had radiographic abnormalities of the renal arteries or kidneys that were perceived as contraindications for kidney donation, compared with 38 (11%) of 333 (42), 5 (4.0%) of 126 (16), and 3 (1.9%) of 159 (43) in other studies that used CT angiography/urography. This discrepancy between centers suggests a need for further research on the clinical relevance of these abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…CT angiography is a proven tool in this domain. It also has the ability to detect parenchymal abnormalities and calculi; however, its use of ionising radiation is a disadvantage that should be considered when evaluating a donor population [11,12].Balanced steady-state free precession (SSFP) MRA provides a high signal-to-noise ratio (SNR) of blood and a unique T 1 /T 2 weighting [13]. SSFP MRA is a noncontrast technique that has been used for the imaging of renal vasculature in several studies [14][15][16].…”
mentioning
confidence: 99%
“…CT angiography is a proven tool in this domain. It also has the ability to detect parenchymal abnormalities and calculi; however, its use of ionising radiation is a disadvantage that should be considered when evaluating a donor population [11,12].…”
mentioning
confidence: 99%
“…MSCT provides a tool for the CT examination of the renal artery, and improves the accuracy and sensitivity of the detection of renal artery variation (Laugharne et al, 2007). However, the MSCT scanning technique and post-processing procedures are not uniform, and this reduces the advantages of the procedure.…”
Section: Discussionmentioning
confidence: 99%